2020
DOI: 10.1007/s00216-020-02923-y
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of photocatalyzed isomerization reactions on a microchip flow reactor by IR-MALDI ion mobility spectrometry

Abstract: The visible-light photocatalytic E/Z isomerization of olefins can be mediated by a wide spectrum of triplet sensitizers (photocatalysts). However, the search for the most efficient photocatalysts through screenings in photo batch reactors is material and time consuming. Capillary and microchip flow reactors can accelerate this screening process. Combined with a fast analytical technique for isomer differentiation, these reactors can enable high-throughput analyses. Ion mobility (IM) spectrometry is a cost-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A photochemical microchip reactor was used in combination with an ion mobility spectrometer for the quick catalyst screening of a photocatalyzed E–Z isomerization . The microchip with a total internal volume of 560 nL (20 μm depth, 100 μm width) was irradiated by a 404 nm LED light for the photocatalyzed E–Z isomerization of an ethyl-cinnamate derivative (Scheme ).…”
Section: Flow Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A photochemical microchip reactor was used in combination with an ion mobility spectrometer for the quick catalyst screening of a photocatalyzed E–Z isomerization . The microchip with a total internal volume of 560 nL (20 μm depth, 100 μm width) was irradiated by a 404 nm LED light for the photocatalyzed E–Z isomerization of an ethyl-cinnamate derivative (Scheme ).…”
Section: Flow Photochemistrymentioning
confidence: 99%
“…A photochemical microchip reactor was used in combination with an ion mobility spectrometer for the quick catalyst screening of a photocatalyzed E−Z isomerization. 391 The microchip with a total internal volume of 560 nL (20 μm depth, 100 μm width) was irradiated by a 404 nm LED light for the photocatalyzed E−Z isomerization of an ethylcinnamate derivative (Scheme 36). The applied flow photochemical setup allowed for two major advantages compared to standard batch setups: first, the real-time analysis and short irradiation times needed for the reaction allowed for the identification of the best catalysts in only minutes.…”
Section: Photoisomerizationsmentioning
confidence: 99%
“…Under some circumstances, ion mobility spectrometry (IMS) can serve as an alternative to mass spectrometry for additional orthogonal separation after chromatography. Ion mobility spectrometers have become a widely used instrument in many analytical and bioanalytical applications. Although the origin of IMS was gas-phase analysis, IMS has been successfully coupled to liquid-phase ionization techniques including electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI) for monitoring of chemical and biochemical reactions or the analysis of aqueous samples. Most IMS designs operate at ambient pressure, making the IMS highly portable.…”
Section: Introductionmentioning
confidence: 99%
“…57 Very recently, IMS was also applied for monitoring photocatalyzed isomerization reactions performed on a continuous-flow microchip reactor. 59 Since IMS systems are very compact and robust, we have high expectations for their use as label-free detection systems in droplet microfluidics. Since ion separation does not take place in vacuum, the risk of contamination should be significantly lower than with MS. And even if oil or detergents enter the drift tube, cleaning is very simple.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, IMS has experienced a renaissance, especially through the combination with electrospray mass spectrometers and the commercial availability of corresponding instruments. While such IMS-MS systems are extremely powerful analytical tools, they have lost the advantages of stand-alone IMS systems such as their small size, instrumental simplicity, robustness, and comparatively low cost. Typical drift tube IMS, for example, has a tube length of only 5–20 cm and can nowadays already be 3D-printed. Although the main focus of IMS is still presented in the gas-phase analysis, it has been demonstrated that IMS is an attractive detector for monitoring liquid-phase chemical and biochemical reactions. Zühlke et al presented a qualitative and quantitative determination of all reaction components of an organic three-step synthesis . Very recently, IMS was also applied for monitoring photocatalyzed isomerization reactions performed on a continuous-flow microchip reactor …”
Section: Introductionmentioning
confidence: 99%